2011
DOI: 10.1002/rra.1335
|View full text |Cite
|
Sign up to set email alerts
|

Differences in river ecological functions due to rapid channel alteration processes in two California rivers using the functional flows model, part 2—model applications

Abstract: 20This study applies the functional flows model that integrates hydrogeomorphic processes and 21 ecological functions to assess physical habitat. Functional flows are discharge values that serve 22 ecological uses. The model was adjusted to evaluate gravel-bed riffle functionality for fall-run 23 2 Chinook salmon with respect to river rehabilitation on the Mokelumne River and flood-induced 1 channel change on the Yuba River. The goal was to test if differences in ecological performance 2 were traceable to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Two of three sub-catchments do not have large dams, so winter floods and spring snowmelt commonly cause spill over Englebright sufficient to exceed the bankfull channel in Timbuctoo Bend. The one regulated sub-catchment does have a large dam, New Bullards Bar (closed in 1970), and this reduces the frequency and duration of floodplain inundation compared to the pre-dam record (Escobar-Arias and Pasternack, 2011;Cienciala and Pasternack, 2016), but it is not like other rivers where the entire upstream watershed is regulated. Sawyer et al (2010) reported the 1.5-year recurrence interval for the post-Englebright, pre-New Bullards Bar period as 328.5 m 3 s −1 and then for post-New Bullards Bar as 159.2 m 3 s −1 .…”
Section: River Contextmentioning
confidence: 99%
“…Two of three sub-catchments do not have large dams, so winter floods and spring snowmelt commonly cause spill over Englebright sufficient to exceed the bankfull channel in Timbuctoo Bend. The one regulated sub-catchment does have a large dam, New Bullards Bar (closed in 1970), and this reduces the frequency and duration of floodplain inundation compared to the pre-dam record (Escobar-Arias and Pasternack, 2011;Cienciala and Pasternack, 2016), but it is not like other rivers where the entire upstream watershed is regulated. Sawyer et al (2010) reported the 1.5-year recurrence interval for the post-Englebright, pre-New Bullards Bar period as 328.5 m 3 s −1 and then for post-New Bullards Bar as 159.2 m 3 s −1 .…”
Section: River Contextmentioning
confidence: 99%
“…Ecosystem functions related to salmonid habitat can be split into (a) bed occupation functions, which occur while the fish are directly interacting with the channel bed (i.e., spawning, incubation, and emergence), and (b) bed preparation functions, which occur between occupation periods during migration (Escobar‐Arias & Pasternack, ). A stable bed, indicated by low shear stress ( τo*0.25em < τ c 50 ), is needed to minimize scour during bed occupation (October–March), whereas high shear stress capable of mobilizing the active layer ( τo*>τc0.25em50true) is necessary to rejuvenate the sediment during bed preparation (April–September) (Konrad, Booth, Burges, & Montgomery, ; Soulsby, Youngson, Moir, & Malcolm, ).…”
Section: Methodsmentioning
confidence: 99%
“…An archetype refers to a simple example exhibiting typical qualities of a particular group without the full local variability distinguishing members of the same group (Cullum, Brierley, Perry, & Witkowski, ). An archetype‐based analysis of the Yuba River, California, was employed by Escobar‐Arias and Pasternack (), who evaluated salmonid habitat conditions across archetypal 1D cross sections. An emerging technique for synthesizing digital terrain models (DTMs) of river corridors using mathematical functions (Brown, Pasternack, & Wallender, ) provides an opportunity to expand on the work of Escobar‐Arias and Pasternack () to evaluate 2D hydraulic response across any channel or floodplain morphology of interest without a major increase in data requirements.…”
Section: Introductionmentioning
confidence: 99%
“…salmonid rearing habitat; Lane et al, 2018). Studies on river flow–form–function linkages using archetypal approaches typically involve either (1) manually manipulating surveyed topography (Brown & Pasternack, 2009; Escobar‐Arias & Pasternack, 2011; Jackson et al, 2015; Sear & Newson, 2004) or (2) synthesizing a river archetype with user‐defined geomorphic attributes (Anim et al, 2019; Cardenas, 2009; Lane et al, 2018; Lee et al, 2020; Trauth et al, 2013). In one example of the former approach, Escobar‐Arias and Pasternack (2011) evaluated the gravel‐bed riffle functionality for salmonid habitat at several channel cross‐sections on the Yuba River, California.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on river flow–form–function linkages using archetypal approaches typically involve either (1) manually manipulating surveyed topography (Brown & Pasternack, 2009; Escobar‐Arias & Pasternack, 2011; Jackson et al, 2015; Sear & Newson, 2004) or (2) synthesizing a river archetype with user‐defined geomorphic attributes (Anim et al, 2019; Cardenas, 2009; Lane et al, 2018; Lee et al, 2020; Trauth et al, 2013). In one example of the former approach, Escobar‐Arias and Pasternack (2011) evaluated the gravel‐bed riffle functionality for salmonid habitat at several channel cross‐sections on the Yuba River, California. They manually modified the high‐resolution topography to generate and compare an alternative channel terrain without riffle‐pool sequences using a computer‐assisted drafting (CAD) program and ArcGIS.…”
Section: Introductionmentioning
confidence: 99%